Protective role of serum albumin in dementia: a prospective study from United Kingdom biobank - Cui, Yiyuan; Li, Chunyu; Ke, Bin; Xiao, Yi; Wang, Shichan; Jiang, Qirui; Zheng, Xiaoting; Lin, Junyu; Huang, Jingxuan; Shang, Huifang (Frontiers in Neurology, 2024)
A number of studies have explored the link between neurodegenerative disorders (NDDs) and albumin, the main protein in human plasma. However, the results have been inconsistent, highlighting the necessity for a detailed systemic analysis.Methods: Utilizing data from the UK Biobank, we investigated the relationship between baseline levels of serum and urine albumin and the occurrence of common NDDs, including Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS) and dementia, employing Cox proportional hazards regression analysis.Our results reveal that elevated baseline serum albumin levels are linked to a decreased risk of developing dementia (beta=-0.024, SE=0.004, P<0.001). Subgroup and interaction analyses highlighted the impact of factors like body mass index (BMI), age, and alcohol consumption on this relationship. Specifically, participants with higher BMI, younger age, or lower alcohol intake exhibited a stronger protective effect. On the other hand, a higher baseline level of urine microalbumin was connected to a slight increase in dementia risk (beta=0.003, SE=3.30E-04, P<0.001). No significant associations were found between albumin levels and the risk of PD or ALS.Our study underscores the potential role of serum albumin as a biomarker associated with reduced dementia risk. These findings contribute valuable insights into the understanding of albumin's impact on NDDs, suggesting its utility as a biomarker for dementia in clinical settings and informing future therapeutic strategies in clinical trials.